Rasionalitas Penggunaan Obat Pada Pasien GERD di Instalasi Rawat Jalan Rumah Sakit - Nurul Aisiyah; Muhammad Akib Yuswar; Nera Umilia Purwanti (Journal Syifa Sciences and Clinical Research, 2022)
The prevalence of Gastroesophageal Reflux Disease (GERD) is increasing every year. Inaccuracy of indication, drug, dose, route of administration, and time interval of administration can lead to failure of therapy. The purpose of this study was to evaluate the rationality of drug use in GERD patients in the outpatient installation of RSUD dr. Soedarso Pontianak. This research method is descriptive observational with cross sectional design. Data collection was carried out retrospectively by looking at the medical records and prescriptions of GERD patients for the period 2020-2021. The samples used in the study were 60 samples that met the inclusion criteria. The results showed that the percentage of rationality in patients without comorbidities was based on 100% correct indication, 93,33% correct drug, 100% correct dose, 100% correct route of administration, and 100% right time interval for administration and with comorbidities based on correct indication 100%, 40% right drug, 100% right dose, 100% right route of administration, and 100% right time interval for administration.